2015
DOI: 10.1534/genetics.115.178046
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Mosaicism Induced by Chemical Treatment of Sperm inDrosophila melanogaster

Abstract: Accurate interpretation of forward genetic screens of chromosomes exposed in mature spermatozoa to a mutagenic chemical requires understanding-incomplete to date-of how exposed chromosomes and their replicas proceed through early development stages from the fertilized ovum to establishment of the germline of the treated male's offspring. We describe a model for early embryonic development and establishment of the germline of Drosophila melanogaster and a model-validating experiment. Our model proposes that, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Conversely, in female inheritance conditions, the indels seem to be generated in the syncytial blastoderm embryo before cellularization of the~3 primordial pole-cell precursors that have been estimated to be set aside for the germline at the 128-cell stage 29 . In fact, at the white locus, we observed only a single indel per female germline, which combined with the~50% inheritance measured for the gRNA transgene and the fully w-F 1 female phenotype, suggests that Cas9 action occurs efficiently at the zygote stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, in female inheritance conditions, the indels seem to be generated in the syncytial blastoderm embryo before cellularization of the~3 primordial pole-cell precursors that have been estimated to be set aside for the germline at the 128-cell stage 29 . In fact, at the white locus, we observed only a single indel per female germline, which combined with the~50% inheritance measured for the gRNA transgene and the fully w-F 1 female phenotype, suggests that Cas9 action occurs efficiently at the zygote stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A). Conversely, in female inheritance conditions, the indels seem to be generated in the syncytial blastoderm embryo before cellularization of the ~3 pole cells that have been estimated to be set aside for the germline at the 128 cell stage 27 . In fact, at the white locus, we observe only 1 indel per female germline, which combined with the ~50% inheritance measured for the gRNA transgene and the fully w-F1 female phenotype, suggest that Cas9 action occurs efficiently at the zygote stage ( Fig.…”
Section: Gene Drive Process Reveals Predictable Resistant Allele Formmentioning
confidence: 99%
“…Post facto repair of "old and new" information (proposed in (28)) is ruled out by both cytological and genetic experiments. Yadlapalli and colleagues showed that chromosome strands are not preferentially segregated during the same cell division (male germ stem cells) (29), arguing against preferential labeling of "immortal strands" by some chemical mark, and Dan Lindsley and colleagues showed that chemicallyinduced single-strand lesions are not preferentially retained in germ stem cells (30).…”
Section: Page Of 9 33mentioning
confidence: 99%